Code generation for creating cloze questions in Moodle using Wolfram Mathematica: Generación de código para la elaboración de preguntas tipo cloze en Moodle usando Wolfram Mathematica - Vílchez Quesada, Enrique (2023)
This paper shares the use of a software package developed by the authors using Wolfram Language for automatic code generation with the aim of designing embedded questions (cloze) in learning platforms Moodle. The package has been called “Incrustada” by its creators and it integrates the ability to convert expressions to Moodle LaTeX code, generate displayed responses, true and false responses, single select and multiple with and without LaTeX code, generate case-sensitive or case-insensitive short-answer questions, numeric short-answer questions (statics), and HTML tables with displayed answers, full answers, or a combination of both.